Spinální muskulární atrofie postihující dolní končetiny, dominantně dědičná (SMALED) jako příklad non-5q formy onemocnění - Hemerková, Pavlína; Matulová, Hana; Kunc, Pavel; Pospíšlová, Lenka; Jandura, Jiří (Neurologie pro praxi, 2023)
Spinal muscular atrophy (SMA) is a degenerative disease of the motoneurons of the anterior horns of the spinal cord, which in approximately 95% of cases is caused by a mutation in the SMN1 gene on chromosome 5q13. Progress in genetic testing, particularly next-generation sequencing, has led to the discovery of additional causative genes underlying non-5q forms of SMA. These are very rare and genetically and phenotypically very heterogeneous. One of these subtypes is caused by a mutation in the cytoplasmic heavy chain gene dynein, gene DYNH1C1. It is a form of SMA with dominant involvement of the lower autosomal dominantly inherited and thus described in the literature under the acronym SMALED. Although it is SMA, this phenotype of the disease is only very slowly progressive and does not significantly impair quality of life.
Keywords: dolní končetina; Humans; Neuromuscular Diseases; spinální svalová atrofie; cytoplazmatické dyneiny; Muscle Weakness; Female; mutace; výsledek terapie; lidé; svalová slabost; Gait Disorders, Neurologic; Medical History Taking; předškolní dítě; Lower Extremity; neuromuskulární nemoci; ženské pohlaví; Treatment Outcome; Muscular Atrophy, Spinal; anamnéza; Cytoplasmic Dyneins; Mutation; Child, Preschool; neurologické poruchy chůze